ANALISA CAMPURAN METANOL–PERTALITE TERHADAP KINERJA DAN SUHU KERJA MOTOR - Sugeng Hadi Susilo; M. Fanny Suharono; Hari Rarindo; Hangga Wicaksono (Jurnal Energi dan Teknologi Manufaktur, 2020)
The study aims to determine the effect of using a mixture of methanol add on to pertalite to the performance of gasoline engines, especially injection system with a capacity of 250 cc engine with two cylinders. This research used experimental method with variables used in this research is mixture of pure pertalite (P), mixture of pertalite - methanol 90% - 10% (PM1), mixture of pertalite - methanol 80% - 20% (PM2), mixture of pertalite - methanol 70% - 30% (PM3), mixed pertalite - methanol 60% - 40% (PM4), 50% - 50% (PM5) pertalite - methanol mixtures, pertalite - methanol 40% - 60% (PM6). Variable related in this research is power, torque and working temperature of the engine. The results of this study indicate that the addition of methanol with pertalite fuel tends to produce lower power and torque, while the temperature of the radiator and exhaust system shows that the use of methanol mixture with pertalite fuel can significantly increase the engine temperature of the vehicle.